Compliance Parameters through Risk Analysis Methodology for Strict Liability Mitigation According to the Law Anti- Corruption (12.846 / 2013) Regarding Public Business - Batisti, Beatriz Miranda (2016)
The Law 12,846 / 2013 has the scope to fight it and enable companies to become active agents in this intent. The repressive aspect of the legislation can be mitigated if the company adopts strategies of prevention through compliance programs. The preventive effectiveness of this law will depend on the analysis of legal aspects and business management topics. The risk analysis methodology and the adoption of objective parameters for the management of anti-corruption risks, allows companies to build an integrity program that puts in focus the ethical actions necessary for companies willing to negotiate with the government.